2018
DOI: 10.1111/jon.12546
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Cerebral Hemodynamic Response to Tactile Somatosensory Stimulation

Abstract: Pneumotactile somatosensory stimulation is a potent stimulus that can evoke large, rapid hemodynamic changes, with adaptation between successive stimulus applications. Due to its high temporal resolution, fTCD is useful for identifying quickly evolving hemodynamic responses, and for correlating changes in hemodynamic parameters such as pulsatility index (PI) and CBFV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…18,24 A two-minute window was used for associating detected HITS with specific surgical maneuvers, based on previous transient analysis of CBFV signals. 25 Following the methods of Clark et al, 16 associated HITS counts were obtained by summing all identified HITS from the time of a surgical maneuver's occurrence to two minutes after the maneuver's occurrence (see subsequently for list of maneuvers). If two maneuvers occurred within less than two minutes, only HITS detected in the period between the first and second maneuvers were counted for the first maneuver.…”
Section: High-intensity Transient Signal Detection and Processingmentioning
confidence: 99%
“…18,24 A two-minute window was used for associating detected HITS with specific surgical maneuvers, based on previous transient analysis of CBFV signals. 25 Following the methods of Clark et al, 16 associated HITS counts were obtained by summing all identified HITS from the time of a surgical maneuver's occurrence to two minutes after the maneuver's occurrence (see subsequently for list of maneuvers). If two maneuvers occurred within less than two minutes, only HITS detected in the period between the first and second maneuvers were counted for the first maneuver.…”
Section: High-intensity Transient Signal Detection and Processingmentioning
confidence: 99%
“…The use of sensory input to facilitate adaptive functional neuroplasticity and sensorimotor function, which are primary goals for incorporating taste stimulation into dysphagia rehabilitation, has been well-established using other modalities. For example, repetitive sensory stimulation (RSS) has been associated with rapid increases of blood flow to sensorimotor brain areas [ 63 ]. Further, RSS has been reported to quickly evoke structural and functional neuroplasticity in sensory networks [ 64 , 65 ], and to increase accuracy of skilled movements when applied prior to task performance [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inclusion of short-separation channels for regressing out the extracerebral HR can improve the reliability and accuracy of such experiments. Furthermore, physiological monitoring with a minimal array of EEG electrodes to monitor participant status (i.e., alert, drowsy, sleep) is advisable, as state control can significantly affect cerebral process mechanisms, including HR and blood flow dynamics during somatosensory encoding and motor control [48].…”
Section: Discussionmentioning
confidence: 99%